EVALUATION OF THE ANTIBACTERIAL ACTIVITY OF ESSENTIAL OILS AGAINST E. COLI ISOLATED FROM RABBITS - B, Majda; Barchan, A.; Aarab, A.; Bakkali, M.; Arakrak, A.; Laglaoui, A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The antibacterial activity of essential oils extracted from Origanum compactum, Thymus capitatus, Foeniculum vulgare, and Rosmarinus officinalis was assessed with the well diffusion method and a microbroth dilution assay against E. coli isolated from the carcasses of rabbits. The chemical composition of these essential oils was also determined by gas chromatography coupled with mass spectrometry (GC/MS). The results of this study indicate that essential oils with high phenol content exert a strong antibacterial activity against E. coli. Essential oils of Origanum compactum and Thymus capitatus containing high amounts of the monoterpenoid phenols thymol and carvacrol (68.99% and 95.25% carvacrol composition, respectively) were particularly effective against E. coli  with low values of MIC = 0.3125% v/v and MBC = 0.625% v/v to report. The essential oil of Foeniculum vulgare also possessed  moderate antibacterial activity (MIC = 50 % v/v) with a non-bactericidal effect, while the essential oil of Rosmarinus officinalis was ineffective at the concentrations tested.